Information Retrieval (International Journal of Engineering and Computer Science, 2018)
The field information Retrieval deals with representing, storage and access to information items.IR is the most usual way of information access, mostly due to the increasing widespread of world wide web(WWW).Information Retrieval mainly deals with retrieval of unstructured data, especially textual documents, in response to a query or topic statement, which may itself be unstructured. In this paper we present the introduction to the information Retrieval and focuses on properties, key techniques and term weighting factor of information retrieval.